EC-Earth-Consortium EC-Earth3-ESM-1 model output prepared for CMIP6 CMIP abrupt-4xCO2 ... - EC-Earth OptimESM Partners EC-Earth-OptimESM (Earth System Grid Federation, 2024)
Coupled Model Intercomparison Project Phase 6 (CMIP6) datasets: These data include all datasets published for 'CMIP6.CMIP.EC-Earth-Consortium.EC-Earth3-ESM-1.abrupt-4xCO2' with the full Data Reference Syntax following the template 'mip_era.activity_id.institution_id.source_id.experiment_id.member_id.table_id.variable_id.grid_label.version'. The EC-Earth3-ESM-1 climate model, released in 2024, includes the following components: atmos: IFS cy36r4 (TL255, linearly reduced Gaussian grid equivalent to 512 x 256 longitude/latitude; 91 levels; top level 0.01 hPa) and co2box v1.0 (CO2 box model; global grid), land: HTESSEL (land surface scheme built in IFS) and LPJ-GUESS v4.1.2 (same grid as atmos), landIce: PISM v1.2 (5 km x 5 km for Greenland, 31 levels), ocean: NEMO3.6 (ORCA1 tripolar primarily 1 degree with meridional refinement down to 1/3 degree in the tropics; 362 x 292 longitude/latitude; 75 levels; top grid cell 0-1 m) and MWE v1.0 (Melt Water Emulator; same grid as ocean for Antarctic surroundings), ...